Multi-objective Optimal Design of RV-550E Reducer Cycloid Gear Profile Modification - Wang Quan; Qin Zhengzheng; Zhao Daxing; Wang Jun; Chen Zhilong; Yan Zicheng (Jixie chuandong)
In order to obtain the best overall performance of cycloid profile,a multi-objective optimal design method of cycloid gear profile modification is presented. The cycloidal gear tooth profile equation and modification theory are introduced. The contact force of the cycloidal gear tooth surface is calculated. A multiobjective optimization model with considering the meshing characteristics of the cycloidal gear and the contact force of the tooth surface is established. The NSGA-Ⅱ algorithm is used to solve the multi-objective optimal problem,and compared with the optimal method of the least contact force of the tooth surface of the cycloidal gear. The results indicate that the fitting degree of this method and the angle modification tooth profile is improved by 3. 99 times,compared with the optimization method with the highest degree of fitting to the angle modification tooth profile,the contact force of the tooth surface of the method is reduced by 4. 98%. The multi-objective synthesis optimum of cycloid is achieved,and the feasibility and superiority of this method is proved.